Quietly in their sleep eaudiobook - Leon, Donna (Commissario Brunetti, 2018)
In the sixth book featuring Donna Leon's ever-charming and sympathetic protagonist, Commissario Guido Brunetti comes to the aid of a young nursing sister who has had five patients unexpectedly die and decides to leave her convent. In the course of his inquiries, Brunetti encounters an unusual cast of characters but discovers nothing that seems criminal. Is the nun simply creating a smoke screen to justify abandoning her vocation? Or has she stumbled onto something very real and very sinister-something that places her own life in imminent danger? A beautiful, suspense-filled novel, Quietly in Their Sleep is Donna Leon at the top of her form.